2016
DOI: 10.1002/ejlt.201600066
|View full text |Cite
|
Sign up to set email alerts
|

Protein and lipid oxidation affect the viscoelasticity of whey protein layers at the oil–water interface

Abstract: Protein and lipid oxidation are prevailing issues that negatively affect the nutritional and sensory quality of food emulsions. It is probable that such oxidative modifications affect the functional properties of proteins, and in particular their ability to form densely packed, interconnected viscoelastic films at the oil–water interface. However, these aspects have hardly been investigated. We induced controlled levels of protein and lipid oxidation using whey protein solution and sunflower oil as substrates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 81 publications
4
29
0
Order By: Relevance
“…This means that LOOHs are prone to accumulate at the lipid–water interface. Likewise, Berton‐Carabin et al . showed that oxidized stripped sunflower oil decreases the tension at the interface formed with water, while the parent non‐oxidized stripped oil does not.…”
Section: Toward Space‐resolved Models: the Necessary First Stepmentioning
confidence: 98%
“…This means that LOOHs are prone to accumulate at the lipid–water interface. Likewise, Berton‐Carabin et al . showed that oxidized stripped sunflower oil decreases the tension at the interface formed with water, while the parent non‐oxidized stripped oil does not.…”
Section: Toward Space‐resolved Models: the Necessary First Stepmentioning
confidence: 98%
“…Moreover, oxidation causes physical changes to the emulsion structures, e.g., polymerization of lipids and eruption of emulsions. 12 Thus, lipids should be protected against oxidation, and at the same time, the interfacial structure may be protected. The rate of oxidation is dependent on the amount and type of oil, emulsifiers, and stabilizers, and on the partitioning of the emulsifier and stabilizer between the interface and continuous phase.…”
mentioning
confidence: 99%
“…Additionally, advanced oxidative damage to proteins may lead to reduction in physical stability. It has been reported earlier that while moderate oxidation helps increase emulsifying activity of proteins, extensive oxidation weakens protein network at the interfacial layer and leads to lower emulsion stability through aggregation [48][49][50]. Higher physical stability of emulsions kept at 6 °C support this outcome.…”
Section: Tryptophan Fluorescence and Protein Oxidationmentioning
confidence: 72%